2021
DOI: 10.1002/biof.1714
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Alzheimer's disease and beneficial action of luteolin

Abstract: Alzheimer's disease (AD), already the world's most common form of dementia, is projected to continue increasing in prevalence over the next several decades. The current lack of understanding of the pathogenesis of AD has hampered the development of effective treatments. Historically, AD research has been predicated on the amyloid cascade hypothesis (ACH), which attributes disease progression to the build-up of amyloid protein. However, multiple clinical studies of drugs interfering with ACH have failed to show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 179 publications
1
28
0
Order By: Relevance
“…We found that, similar to luteolin, SP600125 reduced the phosphorylation of JNK and its downstream signaling and that inhibition of JNK with Luteolin significantly reduced the expression of JNK and of the inflammatory and apoptotic markers, showing a role of JNK in the neuroprotective effects of Luteolin. The anti-inflammatory effects of Luteolin are in agreement with those reported in previous studies on Luteolin [46]. The inhibition of p-JNK through Luteolin was also confirmed by another study conducted on amyloid beta-treated cortical neurons and LPS-stimulated microglial cells [47,48].…”
Section: Discussionsupporting
confidence: 90%
“…We found that, similar to luteolin, SP600125 reduced the phosphorylation of JNK and its downstream signaling and that inhibition of JNK with Luteolin significantly reduced the expression of JNK and of the inflammatory and apoptotic markers, showing a role of JNK in the neuroprotective effects of Luteolin. The anti-inflammatory effects of Luteolin are in agreement with those reported in previous studies on Luteolin [46]. The inhibition of p-JNK through Luteolin was also confirmed by another study conducted on amyloid beta-treated cortical neurons and LPS-stimulated microglial cells [47,48].…”
Section: Discussionsupporting
confidence: 90%
“…Resveratrol has been found to modulate levels of Aβ and certain inflammatory markers in AD patients [172]. Luteolin can play a prophylactic role against AD [173]. Additionally, moderate activation of microglia is thought to have beneficial effects in removing neurotoxins, cellular debris, and dying cells or in promoting neuronal survival.…”
Section: Potential Strategies Involving Cytokines For Management Of Admentioning
confidence: 99%
“…Both flavonoids have broad anti-viral properties, inhibit entry of the virus into host cells, 108,147,148 inhibit neuroinflammation, 149 and reduce cognitive decline. 150 Furthermore, luteolin better penetrates into the brain, inhibits both microglia 151,152 and mast cells, 153,154 and has been reported to reduce neuroinflammation 145,155,156 and cognitive dysfunction, 157,158 including Alzheimer's disease in humans 159,160 and in animal models. 161 Luteolin and quercetin are difficult to absorb after oral administration, 162 but their pharmacokinetics are greatly improved in liposomal preparations using olive pomace oil.…”
Section: Treatment Approachesmentioning
confidence: 99%